2003
DOI: 10.1093/emboj/cdg172
|View full text |Cite
|
Sign up to set email alerts
|

A bacterial collagen-binding domain with novel calcium-binding motif controls domain orientation

Abstract: The crystal structure of a collagen-binding domain (CBD) with an N-terminal domain linker from Clostridium histolyticum class I collagenase was determined at 1.00 A resolution in the absence of calcium (1NQJ) and at 1.65 A resolution in the presence of calcium (1NQD). The mature enzyme is composed of four domains: a metalloprotease domain, a spacing domain and two CBDs. A 12-residue-long linker is found at the N-terminus of each CBD. In the absence of calcium, the CBD reveals a beta-sheet sandwich fold with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
148
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(155 citation statements)
references
References 35 publications
7
148
0
Order By: Relevance
“…The native spectrum of CBD has only one-emission maxima at 317 nm. This comes from solvent-exposed tyrosine residues with the tryptophan being buried inside the core (no emission maxima at 350 nm) (6). The emission spectrum of CBD-collagenous peptide complex was identical to the native CBD spectrum, indicating that the tertiary structure of CBD does not change upon binding to tropocollagen (supplemental Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The native spectrum of CBD has only one-emission maxima at 317 nm. This comes from solvent-exposed tyrosine residues with the tryptophan being buried inside the core (no emission maxima at 350 nm) (6). The emission spectrum of CBD-collagenous peptide complex was identical to the native CBD spectrum, indicating that the tertiary structure of CBD does not change upon binding to tropocollagen (supplemental Fig.…”
Section: Resultsmentioning
confidence: 96%
“…CBD also binds to collagenous peptides with triple helical conformation but not to collagenous peptides that lack triple helix or to gelatin (denatured collagen), suggesting that the CBD-collagen interaction is conformation-specific (4,5). Calcium ions enhance the binding at physiological concentration, and x-ray crystal structures of CBD have been solved in the presence and absence of calcium (6).…”
Section: ؉mentioning
confidence: 99%
“…In the all-β class, the highest-scoring pair (SVM score 7.59, probability 0.97) is the Clostridium histolyticum class I collagenase collagen-binding domain (CBD) 38 and the Clostridium stercorarium putative xylanase carbohydrate-binding module CBM6-3. 39 As shown in Fig.…”
Section: High-scoring Pairs Between Scop Classes Folds or Superfamimentioning
confidence: 99%
“…The definition of which interactions are favorable to the inhibiting effect depends on the knowledge of which groups of the active site are important for the enzymatic activity. In the case of Clostridium histolyticum collagenase, Wilson et al [13] identified the amino acids residues relevant for the enzymatic activity, through the analysis of the mutagenesis effect of each residue upon such activity. The authors concluded that:…”
Section: Resultsmentioning
confidence: 99%